The equine nurse's approach to arthroscopic surgery: part 3. Issue 1 (24th November 2020) - Ryan, Jackie; Johnson, Jessica P.
Abstract: ABSTRACT: The equine veterinary nurse plays a crucial role in the preparation of equine patients for arthroscopic procedures. In this Part 3 of a 3-part series, we aim to provide a practical resource for equine nurses, covering aspects such as pre-operative planning, positioning and aseptic preparation of the equine patient undergoing an arthroscopic procedure.